About a New Model of Engineering Training - A. A. Sysoev; E. B. Vesna; Yu. I. Aleksandrov (Высшее образование в России, 2019)
The aim of the article is to present a model of training engineers based on new approaches to engineering education, taking into account the modern achievements of psychology. The authors believe that the main reason for the insufficient level of engineering training is the discrepancy between the essence of the knowledge transferred to students (both form and content) to the specifics of engineering activity. Therefore, the most important task is to eliminate this contradiction. The basis of the proposed model of engineering training is the design of the educational process in the logic of engineering process in the development of innovative technology. This learning technology called “Simulation-Activity Technology of Engineering Training” (SATET) has been developed and tested at the National Research Nuclear University MEPhI in training engineersdevelopers of innovative technology. The foundations laid in the proposed technology of engineering training, and the mechanisms for its implementation can be considered as a start for the development of a new paradigm of training engineers.